2008
DOI: 10.1016/j.chembiol.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A Structural View of the Inactivation of the SARS Coronavirus Main Proteinase by Benzotriazole Esters

Abstract: The main proteinase (M(pro)) of the severe acute respiratory syndrome (SARS) coronavirus is a principal target for the design of anticoronaviral compounds. Benzotriazole esters have been reported as potent nonpeptidic inhibitors of the enzyme, but their exact mechanism of action remains unclear. Here we present crystal structures of SARS-CoV M(pro), the active-site cysteine of which has been acylated by benzotriazole esters that act as suicide inhibitors. In one of the structures, the thioester product has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 58 publications
5
93
1
1
Order By: Relevance
“…23,24 In particular, reaction of the proteinase with 1-(4-dimethylaminobenzoyloxy)-benzotriazole results in acylation of the catalytic Cys with 1-(4-dimethylaminobenzoyloxy) (PDB code 2V6N), which is very similar to the covalent adduct that we observe. Donation of electrons from the amino substituent toward the dimethylaminobenzoyloxy thioester is thought to render the adduct resistant to hydrolysis.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…23,24 In particular, reaction of the proteinase with 1-(4-dimethylaminobenzoyloxy)-benzotriazole results in acylation of the catalytic Cys with 1-(4-dimethylaminobenzoyloxy) (PDB code 2V6N), which is very similar to the covalent adduct that we observe. Donation of electrons from the amino substituent toward the dimethylaminobenzoyloxy thioester is thought to render the adduct resistant to hydrolysis.…”
mentioning
confidence: 62%
“…Donation of electrons from the amino substituent toward the dimethylaminobenzoyloxy thioester is thought to render the adduct resistant to hydrolysis. 23,24 Analogous electronic effects may be at work in our case and may help explain why DEAB is an inactivator of ALDH7A1, whereas benzaldehyde is a substrate. 20 Alternatively, or at the same time, interactions of DEAB with active site residues may serve to disable the enzyme's hydrolytic machinery.…”
mentioning
confidence: 89%
“…(12)) [119]. Interestingly, investigation of the inhibition properties of aryl benzotriazole esters [118] revealed that a complete inhibition could not be achieved in the absence of electron-donating substituents in the aryl group that would reduce the electrophilicity of the carbonyl C atom in the thioester product [119]. This is likely related to the comparably high susceptibility of thioesters to become hydrolysed by attack of water molecules present in the environment.…”
Section: The Sars-coronavirus Main Proteinasementioning
confidence: 94%
“…As suggested by crystal structure determination of the corresponding reaction product covalently bound to SARSCoV M pro , the nucleophilic Cys 145 attacks the benzotriazole ester carbonyl carbon, and after subsequent cleavage of the tetrahedral intermediate, the corresponding hydroxybenzotriazole moiety acts as a leaving group, leading to a Cys 145 side chain covalently inactivated by thioester formation (Fig. (12)) [119]. Interestingly, investigation of the inhibition properties of aryl benzotriazole esters [118] revealed that a complete inhibition could not be achieved in the absence of electron-donating substituents in the aryl group that would reduce the electrophilicity of the carbonyl C atom in the thioester product [119].…”
Section: The Sars-coronavirus Main Proteinasementioning
confidence: 98%
“…Virtual screening (Plewczynski et al, 2007;Mukherjee et al, 2008;Nguyen et al, 2011) or a high-throughput screening of small molecule libraries have identified inhibitorsincluding an anti-HIV agent and serotonin antagonist, cinanserin (Blanchard et al, 2004;Kao et al, 2004;Wu et al, 2004a;Chen et al, 2005). Other 3CL protease inhibitors identified so far belongto categories such as plant derived phenolic or flavonoid compounds (Lin et al, 2005;Nguyen et al, 2012), active site, nonactive site or competitive inhibitors (Kaeppler et al, 2005;Lee et al, 2005;Du et al, 2007;Ryu et al, 2010), ketones or ester based inhibitors (Goetz et al, 2007;Zhang et al, 2007;Ghosh et al, 2008;Shao et al, 2008;Verschueren et al, 2008;Zhang et al, 2008), modified peptidomimetic inhibitors (Ghosh et al, 2007), metal conjugated inhibitors (Lee et al, 2007;…”
Section: Viral Protease Inhibitorsmentioning
confidence: 99%